THE RELATIONSHIP BETWEEN MARITIME ENGLISH CADETS’ OCEAN LITERACY AND ECOLOGICAL WORLDVIEWS - Nurmailis Nurmailis; Siti Raudhah Maidari; Uchy Mukho Adrianty; Pangkuh Ajisoko; Yudha Aviratri (JEE (Journal of English Education), 2026)
Maritime English education plays an essential role in developing both professional competence and environmental awareness among future seafarers. Despite its significance, limited research has examined its relationship with environmental responsibility, particularly in relation to ocean literacy and ecological worldview. This study investigated the relationships among Maritime English competence, ocean literacy, and ecological worldview among cadets at Malahayati Maritime Polytechnic, Indonesia. A quantitative correlational design was employed involving 48 cadets. Data were collected using a Maritime English questionnaire, an Ocean Literacy instrument, and the Revised New Ecological Paradigm (NEP) Scale. Spearman correlation analysis revealed significant positive relationships between Maritime English competence and ocean literacy (ρ = 0.421, p < 0.05), Maritime English competence and ecological worldview (ρ = 0.397, p < 0.05), and ocean literacy and ecological worldview (ρ = 0.465, p < 0.01). The findings suggest that Maritime English competence is associated not only with professional communication skills but also with environmental knowledge and ecological attitudes. These results highlight the potential of integrating sustainability-related content into Maritime English instruction to promote environmentally responsible maritime professionals.